Polar Flow Past a Spheroid - Ramkissoon, H. (Engineering Transactions, 1997)
The problem of symmetrical Stokes flow of an incompressible micropolar fluid past a spheroid is considered in the paper. The shape of the spheroid differs slightly from that of a sphere. An explicit expression is obtained for the stream function. The boundary conditions at the spheroid surface allow for a slip of tangential fluid flow velocity.